Wegener Granuloma in the Fourth Ventricle - Berlis, Ansgar; Petschner, Franziska; Bötefür, Ingolf Carl; Spreer, Joachim (American Journal of Neuroradiology, 2003)
Summary: We report the case of a 57-year-old man with a known history of antineutrophil cytoplasmic antibody-positive Wegener granulomatosis with initial involvement of the upper and lower respiratory tract. MR imaging of the brain was performed because of new onset CNS symptoms (nausea, altered mental status). The images revealed a mass in the fourth ventricle. The mass diminished in size after systemic steroid treatment, as shown by follow-up MR imaging. The patient died in acute respiratory distress secondary to pneumonia. Histopathologic findings confirmed a Wegener granuloma of the fourth ventricle.